2008
DOI: 10.1007/978-3-540-70575-8_42
|View full text |Cite
|
Sign up to set email alerts
|

Testing Properties of Sets of Points in Metric Spaces

Abstract: Abstract. Given query access to a set of points in a metric space, we wish to quickly check if it has a specific property. More precisely, we wish to distinguish sets of points that have the property from those that need to have at least an ε fraction of points modified to achieve it. We show one-sided error testers that immediately follow from known characterizations of metric spaces. Among other things, we give testers for tree metrics and ultrametrics which are optimal among one-sided error testers. Our tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The second application is a set of questions on testing various properties of metric spaces, such as testing whether a metric is a tree-metric or ultra-metric. In [Ona08], Onak considers several such properties, for which he gives algorithms whose sampling complexity in main memory is of the form O(α/ǫ + n (β−1)/β /ǫ 1/β ), where α ≥ 1 and β ≥ 2 are constant integers. The additive term n (β−1)/β /ǫ 1/β corresponds to sampling for a specific β-tuple.…”
Section: Applications To Other Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second application is a set of questions on testing various properties of metric spaces, such as testing whether a metric is a tree-metric or ultra-metric. In [Ona08], Onak considers several such properties, for which he gives algorithms whose sampling complexity in main memory is of the form O(α/ǫ + n (β−1)/β /ǫ 1/β ), where α ≥ 1 and β ≥ 2 are constant integers. The additive term n (β−1)/β /ǫ 1/β corresponds to sampling for a specific β-tuple.…”
Section: Applications To Other Problemsmentioning
confidence: 99%
“…The additive term n (β−1)/β /ǫ 1/β corresponds to sampling for a specific β-tuple. Using our techniques for distinctness testing, it can easily be shown that whenever an algorithm from [Ona08] requires O(α/ǫ + n (β−1)/β /ǫ 1/β ) samples, the sample complexity in external memory can be improved to O(α/ǫ + (n/B) (β−1)/β /ǫ 1/β ), provided a single disk block contains B points.…”
Section: Applications To Other Problemsmentioning
confidence: 99%
“…This model where queries are accesses to constraints have also been studied in the case where we wish to test properties of a metric space and queries are access to points (see [Ona08,ADPR00,Ras03]). There are instances of these problems that are also examples of LP-Type problems that we consider.…”
Section: Introductionmentioning
confidence: 99%
“…The additive term n (β−1)/β /ǫ 1/β corresponds to sampling for a specific β-tuple. Using our techniques for distinctness testing, it can easily be shown that whenever an algorithm from [12] requires O(α/ǫ + n (β−1)/β /ǫ 1/β ) samples, the sample complexity in external memory can be improved to O(α/ǫ + (n/B) (β−1)/β /ǫ 1/β ), provided a single disk block contains B points.…”
Section: Introductionmentioning
confidence: 99%
“…The second application is a set of questions on testing various properties of metric spaces, such as testing whether a metric is a tree-metric or ultra-metric. In [12], Onak considers several such properties, for which he gives algorithms whose sampling complexity in main memory is of the form O(α/ǫ + n (β−1)/β /ǫ 1/β ), where α ≥ 1 and β ≥ 2 are constant integers. The additive term n (β−1)/β /ǫ 1/β corresponds to sampling for a specific β-tuple.…”
Section: Introductionmentioning
confidence: 99%